PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI SISTEM INFORMASI MANAJEMEN DAERAH, PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada SKPD Kabupaten Buol) - Langenre, Sahroni S. (Katalogis, 2017)
The aim of the study is to determine variable that influence the quality of financial statements of local government. The quality of financial statement referring to four normative preconditions such as: relevance, reliable, comparable, and understandable. The independent variable include human resource capacity, utilization of local management information system technology, and implementation of government accounting standars. Data collection is done by distributing questionnaire to 53 govermental intitutions in Buol regency and also interviewing head of DPPKAD. Data analyzed with SPSS version 17,0 and microsoft exel. Hytesis tested with multiple linier regresion analysis. The results show that, first, human resource capacyti, utilization of local management information system technology, implementation of gevernment standars simultaneously have positive and signivicant influence on the quality of the local government financial statements. Secon, human resource capacity has no positive and significant influence on the local management information system technology, implementation of government accounting standars partially have positive and significant influence on the quality of the local government financial statements.